Estimation of a portfolio to maximize the expected return using the Kelly criterion in the Colombian stock market [Utilización del criterio Kelly para optimizar la rentabilidad de un portafolio en el mercado accionario Colombiano] (2018)
The main objective of an investor when forming a portfolio of shares, is to obtain a return on the invested capital while distributing the risk. The most popular method so far to do this is the one proposed by Markowitz (Markowitz, 1959), which minimizes the variance of the portfolio for a fixed value of expected return. In this paper, the Kelly criterion is presented as an alternative to Markowitz's in order to maximize the expected return. The process for estimating a portfolio under this methodology is shown using the data of the COLCAP index from the Colombian stock exchange. In this case, it was found that the Kelly criterion gave a much less diversified portfolio with few shares, which generated a greater return than the passive strategy of investing in the COLCAP index. © 2018.